Impact of COPD diagnosis timing on clinical and economic outcomes: the ARCTIC observational cohort study - Larsson,Kjell; Janson,Christer; StÃ¤llberg,BjÃ¶rn; Lisspers,Karin; Olsson,Petter; Kostikas,Konstantinos; Gruenberger,Jean-Bernard; Gutzwiller,Florian S; Uhde,Milica; Jorgensen,Leif; Johansson,Gunnar (International Journal of Chronic Obstructive Pulmonary Disease, 2019)
Kjell Larsson,1 Christer Janson,2 Björn Ställberg,3 Karin Lisspers,3 Petter Olsson,4 Konstantinos Kostikas,5 Jean-Bernard Gruenberger,5 Florian S Gutzwiller,5 Milica Uhde,6 Leif Jorgensen,7 Gunnar Johansson31Work Environment Toxicology, Karolinska Institutet, Stockholm, Sweden; 2Department of Medical Sciences: Respiratory, Allergy and Sleep Research, Uppsala University, Uppsala, Sweden; 3Public Health and Caring Sciences, Family Medicine and Preventive Medicine, Uppsala University, Uppsala, Sweden; 4Novartis AB, Täby, Sweden; 5Novartis Pharma AG, Basel, Switzerland; 6IQVIA, Solna, Sweden; 7IQVIA, Copenhagen, DenmarkPurpose: Assess the clinical and economic consequences associated with an early versus late diagnosis in patients with COPD.Patients and methods: In a retrospective, observational cohort study, electronic medical record data (2000–2014) were collected from Swedish primary care patients with COPD. COPD indicators (pneumonia, other respiratory diseases, oral corticosteroids, antibiotics for respiratory infections, prescribed drugs for respiratory symptoms, lung function measurement) registered prior to diagnosis were applied to categorize patients into those receiving early (2 or less indicators) or late diagnosis (3 or more indicators registered >90 days preceding a COPD diagnosis). Outcome measures included annual rate of and time to first exacerbation, mortality risk, prevalence of comorbidities and health care utilization.Results: More patients with late diagnosis (n=8827) than with early diagnosis (n=3870) had a recent comorbid diagnosis of asthma (22.0% vs 3.9%; P<0.0001). Compared with early diagnosis, patients with late diagnosis had a higher exacerbation rate (hazard ratio [HR] 1.89, 95% confidence interval [CI]: 1.83–1.96; P<0.0001) and shorter time to first exacerbation (HR 1.61, 95% CI: 1.54–1.69; P<0.0001). Mortality was not different between groups overall but higher for late versus early diagnosis, after excluding patients with past asthma diagnosis (HR 1.10, 95% CI: ...